Students’ Perception of the Effectiveness of Project based Learning Methods: A Case Study on Fourth Semester at English Education Study Program - Eldin Curtiel Harefa; Elwin Piarawan Zebua; Riswan Zega; Adieli Laoli (Raja Zulkarnain Education Foundation, 2026)
This study aims to explore students' perceptions of the effectiveness of Project-Based Learning (PjBL) in the English Education Study Program at Nias University. Using a qualitative approach with a case study design, data were collected from 30 fourth-semester students through questionnaires and interviews. The findings reveal that the majority of students have a positive perception of PjBL's effectiveness in enhancing learning outcomes, developing 21st century skills, and increasing motivation and engagement in the learning process. Notably, 96.67% of participants acknowledged that the skills gained through PjBL are beneficial for their teaching practice, emphasizing the method's relevance in connecting theoretical knowledge with practical application.However, challenges such as uneven task distribution within groups and insufficient guidance from instructors were identified as areas needing improvement. The study highlights the importance of instructor involvement in facilitating the PjBL process, where effective guidance and support from educators are crucial for success. Students expressed appreciation for the hands-on experience provided by PjBL but noted feelings of being overwhelmed by group work demands, particularly when responsibilities were not evenly shared.The findings suggest that educators should adopt innovative teaching methods that engage students and prepare them for professional demands. Future research is recommended to expand the participant scope and utilize a mixed-methods approach to gain a more comprehensive understanding of PjBL's impact across various educational contexts. By addressing the identified challenges and leveraging PjBL's strengths, educators can create more effective learning environments that meet students' needs.